2014
DOI: 10.1039/c4ta00584h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface-modified silica nanoparticles attached graphene oxide using isocyanate-terminated flexible polymer chains on the mechanical properties of epoxy composites

Abstract: Surface modified silica nanoparticles attached to graphene oxide using isocyanate terminated flexible chains were used for toughening epoxy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 58 publications
3
38
0
Order By: Relevance
“…Among different studied polymer composites, epoxy‐based composites have been widely explored due to the excellent properties associated with its highly crosslinked microstructure. Epoxy resins, one of the structural polymers are known for their good mechanical and thermal properties, high adhesive strength and electrical insulation, low shrinkage, chemical and corrosion resistance . However, severe brittleness and poor resistance to crack propagation has narrow down the applicability of epoxy‐based materials for various fields.…”
Section: Introductionmentioning
confidence: 99%
“…Among different studied polymer composites, epoxy‐based composites have been widely explored due to the excellent properties associated with its highly crosslinked microstructure. Epoxy resins, one of the structural polymers are known for their good mechanical and thermal properties, high adhesive strength and electrical insulation, low shrinkage, chemical and corrosion resistance . However, severe brittleness and poor resistance to crack propagation has narrow down the applicability of epoxy‐based materials for various fields.…”
Section: Introductionmentioning
confidence: 99%
“…The groups marked in red represented the active groups in each stage. The methoxyl groups of MPTMS were hydrolyzed to form silanol groups, and then the silanol groups were condensed with the hydroxyl groups on the RBC surface, by dehydration during the drying process or hot‐pressing process . After mixing with NBR latex, the mercapto groups on the other side of MPTMS molecule reacted with the CC bonds on the NBR macromolecular chains, during hot‐pressing.…”
Section: Resultsmentioning
confidence: 99%
“…The groups marked in red represented the active groups in each stage. The methoxyl groups of MPTMS were hydrolyzed to form silanol groups, and then the silanol groups were condensed with the hydroxyl groups on the RBC surface, by dehydration during the drying process or hot-pressing process [42].…”
Section: Effect Of Silane Coupling Agent On the Performances Of Rbc/nmentioning
confidence: 99%
“…Many hydroxyl groups of SiO 2 surface not only possess good hydrophilic and compatible with polymer resin, but also provide the reactive sites for further surface modification. Many researchers have reported that the addition of SiO 2 in matrix resin leaded to the obvious enhancements of interfacial strength and bulk performance . Moreover, compared with CNTs or GO, SiO 2 are readily obtainable, much cheaper and possessing of special structure, showing unique advantages for large‐scale industrial production.…”
Section: Introductionmentioning
confidence: 99%